2017
DOI: 10.1016/j.aquabot.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Mass development of monospecific submerged macrophyte vegetation after the restoration of shallow lakes: Roles of light, sediment nutrient levels, and propagule density

Abstract: Mass development of monospecific submerged macrophyte vegetation after the restoration of shallow lakes: roles of light, sediment nutrient levels, and propagule density.Aquatic Botany

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 61 publications
(76 reference statements)
2
35
1
Order By: Relevance
“…Seed banks in shallow lake sediments have often been assumed to be insufficient for recovery of submerged vegetation by germination, due to low numbers of viable seedlings, strong seed dormancy, strict germination cues and the reliance of many species upon vegetative reproduction (Haag, 1983 ; Kautsky, 1990 ; Rodrigo et al, 2013 ; Baldridge and Lodge, 2014 ). In contrast, De Winton et al ( 2000 ) and Verhofstad et al ( 2017 ) have shown that seed banks from even the most degraded lakes are capable of an emergence response and thus offer a potential means to restore vegetation. In our survey, the duration of complete macrophyte loss was often unrecorded, but periods of several decades are common (Tables 1 , 2 ).…”
Section: Discussionmentioning
confidence: 95%
“…Seed banks in shallow lake sediments have often been assumed to be insufficient for recovery of submerged vegetation by germination, due to low numbers of viable seedlings, strong seed dormancy, strict germination cues and the reliance of many species upon vegetative reproduction (Haag, 1983 ; Kautsky, 1990 ; Rodrigo et al, 2013 ; Baldridge and Lodge, 2014 ). In contrast, De Winton et al ( 2000 ) and Verhofstad et al ( 2017 ) have shown that seed banks from even the most degraded lakes are capable of an emergence response and thus offer a potential means to restore vegetation. In our survey, the duration of complete macrophyte loss was often unrecorded, but periods of several decades are common (Tables 1 , 2 ).…”
Section: Discussionmentioning
confidence: 95%
“…Even eutrophication is reflected only partly by key variables measured in the water column (Schneider et al, 2016), whilst macrophytes also depend on sediment quality and nutrient concentrations (Verhofstad et al, 2017). Secondly, and in contrast to phytoplankton, the response of macrophytes to nutrients appears to be mostly indirect, arising from reduced transparency due to shading by phytoplankton and epiphytes, and biotic interactions (Scheffer and van Nes, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These systems are sensitive to alien plant invasions, when there are no native plants present. However, native rooted submerged plants can grow very well under these conditions ( Verhofstad et al, 2017 ), which may prevent invasion. If we would have provided nutrients in the water column in our experiment, and not in the sediment, the free submerged plants would have performed much better, and may have outcompeted the invader, whereas the rooted plants may have performed less well, even though nutrients would have precipitated on the sediment.…”
Section: Discussionmentioning
confidence: 99%